Primary biliary non-Hodgkin's lymphoma: A case report. Issue 22 (4th June 2021) - Wu, Jiamei; Zhou, Yin; Li, Qingshu; Zhang, Jing; Mao, Yun
Abstract: Rationale: Primary biliary non-Hodgkin's lymphoma (PBNHL) is a rare disease with only 41 cases reported since 1982. The incidence of PBNHL in patients with malignant cholangiocarcinoma was 0.6%, and PBNHL accounted for 0.4% of extranodal non-Hodgkin's lymphoma, and only 0.016% of all non-Hodgkin's lymphoma cases. Patient concerns: We present a rare case of PBNHL in a 59-year-old female who had jaundice for 3 days with weight loss and Epstein-Barr virus infection. Initial computed tomography and magnetic resonance imaging showed diffuse thickening wall of bile ducts with corresponding lumen stenosis, blurred fat space around the portal vein, lymphadenopathy, and a normal spleen. These manifestations and images were similar to hilar cholangiocarcinoma. So, the diagnosis of hilar cholangiocarcinoma was initially considered. Diagnoses: Postoperative pathology confirmed the final diagnosis was PBNHL. Interventions: The patient and her family requested to clarify the histologic diagnosis by laparotomy biopsy. Because the biopsy result could not be defined during operation, then right hemihepatectomy and choledochojejunostomy were performed. She did not receive any antitumor treatment. Outcomes: One month after the patient's first examination, both computed tomography and magnetic resonance images showed diminished stenosis of common bile duct and left hepatic duct, but a new mass in segment IV of liver was observed. Unfortunately, the patient died due to disease progression. Lessons: This case reminds us that although PBNHL is rare, making accurate diagnosis difficult preoperatively, PBNHL should be considered when encountering a case with Epstein-Barr virus infection and those typical imaging findings.